Advances in organometallic chemistry - West, Robert, 1928-; Stone, F. Gordon A. (Francis Gordon Albert), 1925- (Advances in organometallic chemistry, 2006)
Almost all branches of chemistry and material science now interface with organometallic chemistry - the study of compounds containing carbon-metal bonds. This widely acclaimed serial contains authoritative reviews that address all aspects of organometallic chemistry, a field which has expanded enormously since the publication of Volume 1 in 1964. * Provides an authoritative, definitive review addressing all aspects of organometallic chemistry * Useful to researchers within this active field and is a must for every modern library of chemistry * High quality research book within this rapidly developing field.